STUDENT'S LANGUAGE POLITENESS IN LEARNING AT SMAN 1 KOTA PASURUAN - Mardiningsih, Mardiningsih; Sulukiyyah, Ana Ahsana El; Imania, Itsnaini Fahmi Islami; Noerlaily, Noerlaily; Santoso, Bambang Herry (Indonesian Journal of Educational Development (IJED), 2023)
This study aims to obtain an objective picture of students' language politeness in learning at SMAN 1 Pasuruan City. The type of research is descriptive qualitative research. The data of this research is in the form of students' language politeness and its context. The data source in this research is the students' speech in learning at SMAN 1 Pasuruan City. The technique of data collection is simak catat technique. The main instrument in this research is the researcher himself. The analysis technique is done through (1) data reduction, (2) data presentation, (3) verification of data analysis results, and (4) conclusion drawing. The results of this study show that the communication made by students in learning at SMAN 1 Pasuruan still maintains language politeness which is shown in the use of tact maxim, generosity maxim, approbation maxim, and agreement maxim. However, students of SMAN 1 Pasuruan also still violate the politeness of approbation maxim and diction errors. The more dominant use of the politeness maxim shows that the students' character in language politeness is still well maintained as a form of maintaining cultural norms.